Karakteristik Fisik Arsitektur Islam pada Bangunan Masjid di Kecamatan Curup Tengah Kabupaten Rejang Lebong - Fitrianita, Indah; Nugroho, Mohammad Nur Dita; Ashary, Amin Shody (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study explores the characteristics of Islamic architecture in Curup Tengah, an area with geographic, cultural, and traditional contexts distinct from the origins of Islamic architecture in Arabia. This study focuses on the adaptation of Islamic architecture to local contexts and community needs, as well as its influence on the appication of Islamic architectural elements in mosques. This study aimed to analyze and describe the characteristics and implementation of Islamic architectural elements, including domes, minarets, calligraphy, geometry, floral motifs, prayer halls, mihrabs, pulpits, porticos, ablution areas, study spaces, ventilation and natural lighting. The methodology employed is qualitative research with a descriptive comparative approach, utilizing data collection through observations, interviews, questionnaires, and relevant literature reviews. The finding indicate that mosques in Curup Tengah generally lack minarets and instead optimize doors and windows for natural ventilation, avoiding the use of artificial cooling systems. The application of Islamic architectural elements in these mosques remains limited, with only eight to twelve of the total thirteen elements being implemented. This research enhances the understanding of how Islamic architectural elements are applied and offers valuable insights for future mosque design in Curup.